(untitled) (Universal International Scientific Journal, 2026)
This article provides a comprehensive analysis of the process of introducing digital technologies into the modern education system, its aspects related to the quality of education, and emerging problems. Along with the advantages of the digital learning environment, its disadvantages, the digital competence of teachers, changes in students’ educational activities, and their impact on educational efficiency are highlighted. Scientific and practical recommendations are also developed to eliminate problems.